Real-Time Payment Systems for Boosting Economic Productivity - Prakash Raju Kantheti; Prof. Stella Bvuma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
More effective, safe, and scalable cross-border payment systems have to be developed in light of the explosive rise of global trade and digital commerce. Digital alternatives that make use of cutting-edge technology like artificial intelligence (AI) are gradually replacing traditional cross-border payment methods, which are often expensive and sluggish. This study examines how real-time analytics driven by AI may revolutionise cross-border payment systems by increasing security, decreasing costs, and speeding up transactions. While analysing the critical trade-off between transaction speed and security, the study looks at sophisticated fraud prevention strategies such rule-based systems and machine learning applications. This article uses in-depth case studies of European and Asian payment networks to demonstrate how payment infrastructure and security measures have evolved. In order to promote better international payment system development, these findings can help transnational corporations (TNCs) invest in technological advancements, improve cross-border payments, increase payment accessibility, offer a variety of payment methods, and track factors that affect payments. Global payment systems have changed significantly throughout time to meet the evolving needs of global commerce and technology breakthroughs. Financial transactions have been completely transformed by real-time payment systems (RTPS), which allow for rapid money transfers between banks, people, and companies. These technologies improve cash flow, lower transaction costs, and promote higher economic efficiency by reducing processing delays. This study looks at how RTPS might boost economic productivity by facilitating corporate processes, promoting financial technology innovation, and assisting small and medium-sized business (SME) expansion. It provides a thorough examination of the system's ability to lower economic friction and promote resilience in both established and developing economies, highlighting its effects on consumer behaviour, cross-border commerce, and financial inclusion. Issues including cybersecurity, system interoperability, and regulatory compliance are also covered, highlighting the need of teamwork to maximise RTPS's broad acceptance.
Keywords: Artificial Intelligence; Small and Medium-Sized Enterprises; Real-Time Payment Systems; Payment Infrastructure; Transnational Corporations; Encouraging Innovation, International Trade; Machine Learning Applications; Cross-Border Payment Processes; Fraud Prevention